MATLAB simulation of Mie scattering by hollow sphere TiO2 for dye solar cell application - Zaine, S.N.A. (American Institute of Physics Inc., 2016)
The capability to capture photons by photoelectrode film of a Dye Solar Cell (DSC) can be improved through improvement of the light harvesting efficiency (LHE). Incorporation of light scattering center in the photoelectrode film has shown promising results in improving the LHE. The scattering center act by extending the optical path length and improving the long-wavelength response of the DSC. One of the potential scattering center is hollow sphere structure. The structure could extend the travel distance of light radiance thus increase the possibility of photon being captured by the dye sensitizer causing more electrons to be excited. The aim of this study is to simulate the effect of the hollow diameter and shell thickness on the scattering efficiency of the TiO2 hollow sphere structure. MATLAB programming was used to simulate the effect based on the Mie Scattering theory. The optimum hollow diameter and shell thickness to obtain high scattering efficiency is approximately 310 nm and 25 nm, respectively if the inner media is iodide electrolyte while 240 nm and 65 nm, respectively if the inner media is air. A hollow sphere structure could improve the scattering of light due to the presence of inner sphere light confinement by the presence of inner sphere's voids. Â© 2016 Author(s).